2020
DOI: 10.1159/000508821
|View full text |Cite
|
Sign up to set email alerts
|

Full-Thickness Macular Hole with Coats Disease: A Case Report

Abstract: We report a case of full-thickness macular hole (FTMH) which developed during follow-up for Coats disease. To our knowledge, this is the first report on a case of FTMH which developed during follow-up for Coats disease. A 17-year-old boy was referred to our institution with blurred vision in his left eye. Fundus examination showed yellowish subretinal exudates with overlying telangiectatic retinal vessels in the temporal periphery in the left eye; the right eye was normal. Fluorescein angiography revealed diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The final visual acuity (VA) was 20/80. Hashimoto et al 7 presented the only case with early closure as well as excellent final VA (20/20).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The final visual acuity (VA) was 20/80. Hashimoto et al 7 presented the only case with early closure as well as excellent final VA (20/20).…”
Section: Introductionmentioning
confidence: 98%
“…In PubMed Medline we found only 7 case reports describing this phenomenon. [1][2][3][4][5][6][7] Some cases were reported before the availability of optical coherence tomography (OCT), and only 3 described surgical treatment. 3,4 Wong et al 4 reported 2 failed attempts to close a macular hole in a child with Coats disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation